EFEKTIVITAS MODEL DISCOVERY LEARNING BERBANTUAN LKPD ELEKTRONIK UNTUK MENINGKATKAN KETERAMPILAN PROSES SAINS DAN SIKAP ILMIAH - Ungirwalu, Shanty Yustin; Zuhdan Kun Prasetyo; Miftahul Jannah (Jurnal Pendidikan Indonesia, 2025)
The problem in this study is the low science process skills (KPS) and scientific attitudes of students in learning science. This is caused by the lack of use of learning models and media that encourage scientific activity and optimal involvement of students. The main objective of this research is to analyze the effectiveness of the discovery learning model assisted by e-worksheets in improving students' science process skills and scientific attitudes. This study used a quantitative approach with a One Group Pretest-Posttest Design. The subjects in this study were 48 seventh grade students who were involved as test subjects. The data collection method used a 10-item multiple choice test to measure KPS and an observation sheet to assess scientific attitudes. The instrument has been tested for validity and reliability using the help of the Quest program. The data were analyzed quantitatively with Wilcoxon Test to test the difference before and after treatment and N-Gain test to determine the ability improvement. The results showed that there was a significant increase in science process skills and scientific attitudes after learning with the discovery learning model assisted by e-worksheets. Thus, it can be concluded that this learning model is effective in building scientific thinking skills and fostering students' scientific attitudes. The implication of this research shows the importance of using discovery-oriented learning models and interactive media in science learning to support the formation of the Pancasila learner profile.